2015
DOI: 10.1088/0960-1317/25/7/074006
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of titanium oxide nanostructures by electron-beam lithography combined with plasma etching

Abstract: Patterning of metal oxide nanostructures with precisely controlled geometries and spacings can play an important role in the improvement of sensors for gas detection. Titanium oxide thin films were deposited on oxidized silicon substrates by reactive magnetron sputtering at room temperature. Patterning of TiO2 nanostructures was conducted by electron beam lithography combined with plasma etching. It was found that for 120 nm-thick TiO2 nanostructure formation, HSQ e-beam resists and Cr films prove to be suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…As an alternative, biomimetic double-scale nano/micro-structures like “moth eye” have been developed to suppress the surface reflection losses ,, and to increase the probability of light trapping and scattering in the active layer of solar cells , because they form linear effective gradient-refractive-index profiles between air and the bulk surface and extend effective optical path lengths due to the diffracted and rebounded lights between micro-structure arrays, resulting in the enhanced device performance. However, the fabrication of these nano/micro-structures often involves expensive and complex processes including electron-beam lithography, , laser interference lithography, nanoimprint lithography, , or photolithography, followed by a dry etching process. Herein, we adopted a facile, cost-effective, and low-temperature chemical bath deposition (CBD) technique and potassium hydroxide (KOH) wet etching process to produce these nano/micro-structures on Si substrate.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, biomimetic double-scale nano/micro-structures like “moth eye” have been developed to suppress the surface reflection losses ,, and to increase the probability of light trapping and scattering in the active layer of solar cells , because they form linear effective gradient-refractive-index profiles between air and the bulk surface and extend effective optical path lengths due to the diffracted and rebounded lights between micro-structure arrays, resulting in the enhanced device performance. However, the fabrication of these nano/micro-structures often involves expensive and complex processes including electron-beam lithography, , laser interference lithography, nanoimprint lithography, , or photolithography, followed by a dry etching process. Herein, we adopted a facile, cost-effective, and low-temperature chemical bath deposition (CBD) technique and potassium hydroxide (KOH) wet etching process to produce these nano/micro-structures on Si substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [18] was shown that direct write e-beam lithographic process and plasma etching allow successful simple fabrication of the TiO 2 nanostructures. The shape and size of resist pillars change in dependence on the resist thickness, distance between the resist pillars, exposure dose, patterned thin film material and its thickness, substrate type and electron energy.…”
Section: Resultsmentioning
confidence: 99%
“…[8] One-dimensional sub-wavelength gratings can be used to enhance Raman scattering intensity. [9] Patterning of TiO 2 [10] nanostructures, for which geometries and spacings can be precisely controlled, may play an important role in the improvement of sensors for gas detection. Different methods [11] have been used to fabricate micro-and nanostructures for research and applications.…”
Section: Introductionmentioning
confidence: 99%